Perceived Toxic Parenting, Self-Esteem And Students’ Academic Achievement;An Analysis of Psychological Point of View And Islamic Perspective - Nurul Hidayah; Angraini Ramli; Fransisca Tassia (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims at analyzing Perceived Toxic Parenting, Self-Esteem And Students’ Academic Achievement. It is a library research. The study analyzed the effect of perceived toxic parenting toward children’ self-esteem and academic achievement from Psychology point of view and islamic perspective. Several literatures related to the topict were analyzed with the keywords used to serach the articles are; Parenting, islamic parenting, toxic parenting, self-esteem, academic achievement. The study found that the toxic parents, one or both parents, results to negative psychological development of children. Children raised by toxic parents are more likely difficult to develop their positive self-image in which lead to lack of self-esteem. Children’s Self-esteem and academic achievement are two correlating variables that support each other. The lower self-esteem children hold, the lower academic achievement they obtained. In addition, Islam enlighted the parents to avoid practicing toxic parenting. Allah Ta’ala rebuked parents in his word in Surah al-An'am 151, that for any reason, parents are prohibited from killing, neglecting, not feeding their children. In a hadith of the Prophet narrated by al-Baihaqi, our Prophet stated that the children also have the right to be treated fairly among their siblings.